Frequency of Dementia in Patients with Amyotrophic Lateral Sclerosis - Shoaib Ahmed, Amjad Hussain Balouch, Mukhtiar Ali Lakho, Muhammad Munwar Ali, Inayatullah Awan, Safdar Hussain Arain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of dementia in patients with amyotrophic lateral sclerosis. Study Design: Cross-sectional study Place and Duration of Study: Department of Neurology, Chandka Medical College Hospital, Larkana Pakistan from 14thJanuary 2019 to 13thJuly 2019. Methodology: One hundred and ten patients were enrolled. Diagnosis was made after patient examination as proposed by memory impairment greater than 1 cognitive-disturbance. Results: The mean age was 54.36±11.12 years and mean duration of disease was 18.46±7.13 months. Sixty seven (61%) were males and 43 (39%) were females. Dementia was found noted in 11 (10%) patients while 99 (90%) was found to benormal. Conclusion: The frequency of dementia in patients with amyotrophic lateral sclerosis was found to considerable.